Soil health management of an Alfisol with INM in direct seeded rice - chickpea system - KUMARI, GEETA; KUMARI, SUNITA; SINGH, K.K.; JAISWAL, AMAN; KOHLI, ANSHUMAN (Journal of Soil and Water Conservation, 2023)
A field experiment on direct seeded rice was conducted at Rice Research Farm, Birsa Agricultural University, Kanke, Ranchi during Kharif 2016-17 and 2017-18 to evaluate the effect of integrated nutrient management on nutrient utilization and soil fertility status under rice- chickpea cropping sequence. The experiment was laid out in randomized block design with three replications. The soil was clay loam in texture, acidic in nature with pH 5.97, low in available N (223.81 kg ha-1), medium in P (23.35 kg ha-1) and K (169.44 kg ha-1) and low in organic carbon (3.9 g kg-1). The experiment comprised of ten treatments viz. control (no fertilizer or manure), 50% RDF, 75% RDF, 100% RDF, 50% RDF +50% N through FYM, 50% RDF + 50% N through vermi compost, 75% RDF +25% N through FYM, 75% RDF+25% N through vermincompost, 100% RDF +25% N through FYM and 100% RDF +25% N through vermin-compost in rice (var. Shbhagidhan) and a second crop, chickpea (var. JG-14) in rabi season sown with seed rate @ 80 kg ha-1 on 50% RDF. The result of the experiment in terms of rice – chickpea cropping sequence revealed that the application of 100% RDF + 25% N through VC in rice in kharif & then in rabi chickpea at 50% recorded the highest production of cropping sequence (94.03 q ha-1), nitrogen uptake (177.43 kg ha-1), phosphorus uptake (22.70 kg ha-1), potassium uptake (170.73 kg ha-1), system net return (Rs. 86650 ha-1) and system B:C ratio (2.59). Among all treatments, the best nutrient management practice i.e, 100% RDF with 25% N through VC in rice in kharif and chickpea in rabi at 50% RDF significantly improved soil chemical properties viz. organic carbon, avail. N, P2O5 and K2O and biological properties i.e SMBC, bacterial, fungal and actinomycetes population after two years of cropping cycle. Hence, optimum application of nutrients either through organic or inorganic sources can be practiced in alfisol under rice-chickpea cropping sequence for higher productivity, profitability, nutrient utilization and also conserve soil health in a long run.